Inert macrocyclic Eu3+ complex with affirmative paraCEST features. Issue 12 (26th March 2020) - Gambino, Tanja; Valencia, Laura; Pérez-Lourido, Paulo; Esteban-Gómez, David; Zaiss, Moritz; Platas-Iglesias, Carlos; Angelovski, Goran
Abstract : Highly kinetically inert paramagnetic platform shows outstanding CEST properties suitable for advantageous MRI applications. Abstract : We report on a macrocyclic platform based on an 18-membered macrocycle that forms kinetically highly inert paramagnetic complexes and possesses an excellent outlook for the development of bioresponsive paraCEST (paramagnetic chemical exchange saturation transfer) contrast agents. The investigated europium(iii ) chelate is non-hydrated and contains four amide groups, each possessing two paramagnetically shifted proton resonances distant from bulk water. The X-ray crystal structure and solution studies indicate that the metal ion is ten-coordinated, being directly bound to the six N atoms of the macrocycle and the four amide O atoms of the pendant arms. The complex presents an excellent inertness with respect to dissociation, being stable under a variety of harsh conditions, including highly acidic and basic media or elevated temperatures. The amide protons are in slow-to-intermediate exchange with bulk water, which gives rise to the generation of a strong CEST effect at low probe concentration and saturation powers (∼25% at 5 mM, B 1 = 5 μT, 37 °C). We demonstrate the potential of this platform for mapping pH in its microenvironment and foresee potential for the development of diverse paraCEST probes and sensors.